Predictors of racial differences in weight loss: the PROPEL trial - Newton, Robert L.; Zhang, Dachaun; Johnson, William D.; Martin, Corby K.; Apolzan, John W.; Denstel, Kara D.; Brantley, Phillip J.; Davis, Terry C.; Arnold, Connie; Sarpong, Daniel F.; Price‐Haywood, Eboni G.; Lavie, Carl J.; et al. (Obesity (Silver Spring, Md.), 2024)
Objective Studies have consistently shown that African American individuals lose less weight in response to behavioral interventions, but the mechanisms leading to this result have been understudied. Methods Data were derived from the PROmoting Successful Weight Loss in Primary CarE in Louisiana (PROPEL) study, which was a cluster‐randomized, two‐arm trial conducted in primary care clinics. In the PROPEL trial, African American individuals lost less weight compared with patients who belonged to other racial groups after 24 months. In the current study, counterfactual mediation analyses among 445 patients in the intervention arm of PROPEL were used to determine which variables mediated the relationship between race and weight loss. The mediators included treatment engagement, psychosocial, and lifestyle factors. Results At 6 months, daily weighing mediated 33% (p = 0.008) of the racial differences in weight loss. At 24 months, session attendance and daily weighing mediated 35% (p = 0.027) and 66% (p = 0.005) of the racial differences in weight loss, respectively. None of the psychosocial or lifestyle variables mediated the race‐weight loss association. Conclusions Strategies specifically targeting engagement, such as improving session attendance and self‐weighing behaviors, among African American individuals are needed to support more equitable weight losses over extended time periods.